SARS-CoV-2 wave two surveillance in East Asia and the Pacific: Longitudinal trend analysis - Post, Lori Ann; Lin, Jasmine S.; Moss, Charles B.; Murphy, Robert L.; Ison, Michael G.; Resnick, Danielle (JMIR Publications, 2021)
The COVID-19 pandemic has had a profound global impact on governments, healthcare systems, economies, and populations around the world. Within the East Asia and Pacific region, some countries have mitigated the spread of the novel coronavirus effectively and largely avoided severe negative consequences, while others still struggle with containment. As the second wave reaches East Asia and the Pacific, it becomes more obvious that additional SARS-CoV-2 surveillance is needed to track recent shifts in the pandemic, rates of increase, and persistence.